International Histopathology Consensus for Unilateral Primary Aldosteronism - Williams, Tracy Ann; Gomez-Sanchez, Celso E; Rainey, William E; Giordano, Thomas J; Lam, Alfred K; Marker, Alison; Mete, Ozgur; Yamazaki, Yuto; Zerbini, Maria Claudia Nogueira; Beuschlein, Felix; Satoh, Fumitoshi; Burrello, Jacopo; et al. (The journal of clinical endocrinology and metabolism, 2021)
Abstract Objective Develop a consensus for the nomenclature and definition of adrenal histopathologic features in unilateral primary aldosteronism (PA). Context Unilateral PA is the most common surgically treated form of hypertension. Morphologic examination combined with CYP11B2 (aldosterone synthase) immunostaining reveals diverse histopathologic features of lesions in the resected adrenals. Patients and Methods Surgically removed adrenals (n = 37) from 90 patients operated from 2015 to 2018 in Munich, Germany, were selected to represent the broad histologic spectrum of unilateral PA. Five pathologists (Group 1 from Germany, Italy, and Japan) evaluated the histopathology of hematoxylin-eosin (HE) and CYP11B2 immunostained sections, and a consensus was established to define the identifiable features. The consensus was subsequently used by 6 additional pathologists (Group 2 from Australia, Brazil, Canada, Japan, United Kingdom, United States) for the assessment of all adrenals with disagreement for histopathologic diagnoses among group 1 pathologists. Results Consensus was achieved to define histopathologic features associated with PA. Use of CYP11B2 immunostaining resulted in a change of the original HE morphology-driven diagnosis in 5 (14%) of 37 cases. Using the consensus criteria, group 2 pathologists agreed for the evaluation of 11 of the 12 cases of disagreement among group 1 pathologists. Conclusion The HISTALDO (histopathology of primary aldosteronism) consensus is useful to standardize nomenclature and achieve consistency among pathologists for the histopathologic diagnosis of unilateral PA. CYP11B2 immunohistochemistry should be incorporated into the routine clinical diagnostic workup to localize the likely source of aldosterone production.